Economic impacts of the maritime silk road initiative on the Suez Canal - Anas Rakha; Khadiga El-Aasar (Journal of Applied Economics, 2024)
The Belt and Road Initiative (BRI) is a key component of China's future international trading network. Through the Suez Canal (SC), the Maritime Silk Road Initiative (MSRI) links China to other parts of Asia, Africa, and Europe, making it a major route for global seaborne trade. This is because of the SC's unique location on the MSRI. This study uses annual data from 1990 to 2022 to examine this dynamic relationship. We use the Vector Auto-Regressive (VAR) model and Impulse Response Function to account for the interaction effect of the variables. Model results show that China's seaborne trade will increase SC trade by 23%, and China's BRI investment projects are anticipated to have a significant impact on SC cargo trade in the medium and long run. Developing more value-added services in adjacent regions and attracting large Chinese investments might make the SC a worldwide logistics and a green energy hub.
Keywords: 330; China's BRI investment projects; Maritime silk road initiative; Suez Canal; VAR model